2016
DOI: 10.1515/amma-2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Knowledge, Attitudes and Practices Regarding Dietary Fats

Abstract: Objective: The purpose of the study was to assess the knowledge, attitudes, and behavior regarding dietary fats among mothers in Romania. Material and methods: A sample of 305 mothers from Romania were included in a cross-sectional observational study. The online questionnaire addressed their knowledge, attitudes, and practices regarding the dietary fats used in their children's diet. The frequencies and proportions of the collected variables were calculated based on respondents' answers. Results: While almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[ 18 ] Literature showed that knowledge of consumers regarding fatty acids and high-fat diet was not acceptable. [ 20 21 ] For example, Valentin et al . reported that 39.7% of mothers know about the difference between saturated and unsaturated fats and only 16.4% of them were able to correctly differentiate hydrogenated from interesterified margarine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] Literature showed that knowledge of consumers regarding fatty acids and high-fat diet was not acceptable. [ 20 21 ] For example, Valentin et al . reported that 39.7% of mothers know about the difference between saturated and unsaturated fats and only 16.4% of them were able to correctly differentiate hydrogenated from interesterified margarine.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the actual ability of mothers to identify foods by their fat content was low and developing maternal nutrition education programs in this field was necessary. [ 20 ] Eckel et al . showed that Americans’ knowledge, especially regarding food sources of SFAs and TFAs was relatively low.…”
Section: Introductionmentioning
confidence: 99%